Optimizing real swine wastewater treatment efficiency and carbohydrate productivity of newly microalga Chlamydomonas sp. QWY37 used for cell-displayed bioethanol production - Qu, Wenying; Loke Show, Pau; Hasunuma, Tomohisa; Ho, Shih-Hsin (Bioresource Technology, 2020)
[Display omitted] •A biomass concentration of 9.9 g/L was achieved in real swine wastewater.•The highest carbohydrate productivity of 944 mg/L·d was obtained.•The highest COD (81%), TN (96%) and TP (nearly 100%) removals were achieved.•Semi-continuous operation was performed together with direct bioethanol production. This work aimed to study an newly isolated microalgal strain, Chlamydomonas sp. QWY37, that can achieve a maximum carbohydrate production of 944 mg/L·d, along with high pollutant removal efficiencies (chemical oxygen demand: 81%, total nitrogen: 96%, total phosphate: nearly 100%) by optimizing culture conditions and using an appropriate operation strategy. Through a cell-displayed technology that utilizes combined engineered system, a maximum microalgal bioethanol yield of 61 g/L was achieved. This is the first report demonstrating the highest microalgal carbohydrate productivity using swine wastewater without any pretreatments associated with direct high-density bioethanol production from the subsequent microalgal biomass. This work may represent a breakthrough in achieving feasible microalgal bioethanol conversion from real swine wastewater.